INVESTIGASI EFEK SOLIDITAS TERHADAP KONTUR TEKANAN SUCTION AREA PADA TURBIN AIR PROPELLER ALIRAN HORISONTAL MENGGUNAKAN COMPUTIONAL FLUID DYNAMIC - Fajar Paundra; Akhmad Nurdin; Febri Budi Darsono (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2022)
Internal parameters of the propeller axial turbine affect the performance of the turbine itself. The influence of the internal parameters will provide information on the characteristics of a turbine design and produce optimal performance. Solidity or the ratio of the gaps between turbine blades to the length of the blade chord is one of the internal parameters that affect the performance of the propeller turbine, and visually has similarities to the number of blades parameter. The object of this study is to observe how the solidity of the propeller turbine affects the water pressure contour on the suction side or pressure water before pounding the blade. This study method uses Computational Fluid Dynamic (CFD) with SolidWorks 2016 Flow Simulation software. The variable number of blades used in this study is 3 to 7 blades, with 200 blades each. The results of this study present a plot or a figure with different color contours for each parameter that shows the value of water pressure on the suction and discharge sides, as well as the pressure contour on the surface turbine. This study shows that the higher the solidity value or the more the number of blades, the water pressure in the suction area will increase.